Suppressor of cytokine signalling 6 is a potential regulator of antimicrobial peptides in the Chinese oak silkworm, Antheraea pernyi. (December 2021) - Abbas, Muhammad Nadeem; Kausar, Saima; Gul, Isma; Ke, Xiao-Xue; Dong, Zhen; Lu, Xiaoqin; Cui, Hongjuan
Highlights: We cloned and characterized the SOCS-6 cDNA from the Chinese oak silkworm Antheraea pernyi. ApSOCS-6 mRNA expresses ubiquitously in various tissues. Microbial challenge affected the expression profiles of the ApSOCS-6 gene. ApSOCS-6 is involved in immune responses via regulating antimicrobial peptides. Abstract: The SOCS/CIS is a family of intracellular proteins distributed widely among living organisms. The members of this family have extensively been studied in mammals and have been shown to regulate various physiological processes. In contrast, the functional roles of SOCS/CIS family proteins are unknown in most invertebrates, including insects. Here, we retrieved a full-length open reading frame (ORF) of SOCS-6 from Chines oak silkworm, Antheraea pernyi (Designated as ApSOCS-6 ), using the RNA-seq database. The predicted ApSOCS-6 amino acid sequence comprised an N-terminal SH2 domain and a C-terminal SOCS-box domain. It shared the highly conserved structures of the SOCS proteins with other lepidopteran species. ApSOCS-6 mRNA transcript was detected in all the tested tissues of the A. pernyi larvae; however, the highest mRNA levels were found in the larval hemocytes, fat bodies, and integuments. The mRNA transcript levels of ApSOCS-6 were increased in the A. pernyi larval hemocytes and fat bodies after a challenge by the Gram-positive bacteria, M. luteus, Gram-negative bacteria, Escherichia coli, Virus, ApNPV, and Fungus, B. bassiana . After the knockdown of ApSOCS-6, we found a significant increase in bacterial clearance and a decrease in the relative replication of bacteria. To evaluate the possible cause of enhanced antibacterial activity, we measured antimicrobial peptides expression in the fat body of A. pernyi larvae. The production of AMPs was strongly increased in the B. cereus infected larval fat bodies following silencing of ApSOCS-6 . Our data indicate that ApSOCS-6 negatively regulates the expression of AMPs in immune tissues in response to the B. cereus challenge.